Characterization of macrophages infiltrating peri‐implantitis lesions. Issue 3 (13th January 2020) - Fretwurst, Tobias; Garaicoa‐Pazmino, Carlos; Nelson, Katja; Giannobile, William V.; Squarize, Cristiane H.; Larsson, Lena; Castilho, Rogerio M.
Abstract: Objectives: The mechanisms involved in the initiation and progression of peri‐implantitis lesions are poorly understood. It was the aim to determine the content and activation status of macrophages present in human peri‐implantitis lesions and compare the current findings with the macrophage polarization associated with periodontitis lesions. Material and Methods: A total of 14 patients were studied in this investigation. Seven were soft tissue biopsies from dental implants affected by peri‐implantitis that required explantation. Seven biopsies were from chronic periodontal disease. Immunofluorescence stains were performed using biomarkers to identify macrophages (CD68 + ) undergoing M1 polarization (iNOS + ) and M2 polarization (CD206 + ), along with Hoechst 33, 342 to identify DNA content. All samples were stained and photographed, and double‐positive cells for CD68 and iNOS or CD68 and CD206 were quantified. Results: All peri‐implantitis biopsies examined revealed a mixed population of macrophages undergoing M1 polarization and M2 polarization. Further analysis demonstrated the co‐expression of iNOS and CD206, which indicates the presence of a heterogenic immune response on peri‐implantitis lesions. Macrophage polarization in peri‐implantitis lesions presents a distinct pattern than in periodontitis. We observed a significant increase in the population of M1 macrophages on peri‐implantitis samples compared to periodontal disease samples. Conclusion: Our results demonstrate that peri‐implantitis has higher numbers of macrophages displaying a distinct macrophage M1 polarization signature compared to periodontitis lesions. This pattern may explain, in part, the distinct nature of peri‐implantitis progression vs. periodontitis in humans.